A double dynamic cross-linked hydrogel for sustained release of coral lactone and its preparation method and application

By using a double dynamic crosslinking network in the hydrogel, the limitations of existing hydrogels in application are solved, and the injectable, self-healing, antibacterial and anti-inflammatory effects are achieved, and wound repair is promoted.

CN116120595BActive Publication Date: 2025-04-15YUEYANG INTEGRATED TRADITIONAL CHINESE & WESTERN MEDICINE HOSPITAL SHANGHAI UNIV OF CHINESE TRADITIONAL MEDICINE
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310089978.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-09
Publication Date
2025-04-15
Estimated Expiration
2043-02-09

AI Technical Summary

Technical Problem

In actual application, existing natural polymer-based hydrogels have limitations such as shedding, tearing, inability to completely fill irregular wound beds and close contact wounds. The manufacturing process of dynamic crosslinked hydrogels is complex, affecting their biocompatibility and biological activity.

Method used

A hydrogel formed by keratin, procatechaldehyde and ferric chloride was used to prepare an injectable, self-healing, antibacterial and anti-inflammatory properties through simple mixing and crosslinking reactions.

Benefits of technology

It realizes the injectability, good viscosity, antibacterial properties, self-healing properties and good biocompatibility of hydrogels, which can promote the repair of skin wound tissues and is suitable for biomedical, tissue engineering and drug delivery fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116120595B_ABST
    Figure CN116120595B_ABST
Patent Text Reader

Abstract

The present invention relates to a method for preparing a double dynamic cross-linked hydrogel for sustained release of choriocarpa lactone and its application in promoting the healing of wounds of inflammatory diseases, and relates to the field of biomedical materials. The double dynamic cross-linked hydrogel dressing for sustained release of choriocarpa lactone is obtained by self-crosslinking a complex prepared by the reaction of protocatechuic aldehyde and ferric chloride and keratin and physically mixing with F127 / F68 mixed micelles loaded with choriocarpa lactone. The hydrogel provided by the present invention is simple and mild to prepare, has sustained release of choriocarpa lactone, is injectable, self-healing, has good viscosity and biocompatibility, and has antibacterial, anti-inflammatory, and pro-proliferation properties, and is a good injectable biomedical hydrogel dressing for promoting the healing of wounds of inflammatory diseases.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of biomedical materials, in particular to a double dynamic cross-linked hydrogel for sustained-release of chorthonia lactone and a preparation method and application thereof. Background Art

[0002] Chronic non-healing wounds are a major complication of diabetes, with high morbidity, amputations, and a huge economic burden. In general, wound healing is a coordinated process with three major phases: inflammation, proliferation, and remodeling, in which macrophages play an important role in the smooth junction of the inflammatory and proliferative phases, which polarize from the M1 phenotype exhibiting typical pro-inflammatory properties to the selectively activated M2 phenotype with anti-inflammatory and tissue regeneration functions. However, due to the presence of excessive glycosylated residues in hyperglycemia and diabetic wounds, macrophages exhibit reduced activity inducing the switch from M1 to M2 phenotype. This leads to the accumulation of M1 macrophages and pro-inflammatory cytokines, while the levels of M2 macrophages and anti-inflammatory cytokines are low, creating a hostile microenvironment for excessive / prolonged inflammation. Therefore, regulating macrophage polarization toward the anti-inflammatory M2 phenotype is a promising strategy for diabetic wound healing.

[0003] Hydrogels have great advantages in wound treatment due to their extracellular matrix-like three-dimensional porous structure, good hydrophilicity and ability to maintain a moist environment on the wound surface, as well as the ability to effectively deliver treatment directly to the wound surface for rapid healing. However, most natural polymer-based hydrogels have some limitations in practical applications. For example, hydrogel dressings may fall off or tear due to frequent body movements and difficulty in fixation, or they may neither completely fill the irregular wound bed nor closely contact the wound to maximize the treatment efficiency. Therefore, the ideal hydrogel dressing is expected to move from a single physical coverage or a single function to a combination of multiple functions, including injectability, self-healing, moderate tissue adhesion, easy dressing change, antibacterial and anti-inflammatory properties, to promote tissue repair in clinical practice.

[0004] Many efforts have been made to explore multifunctional hydrogel dressings. In recent years, dynamic cross-linked hydrogels have attracted attention due to their unique injectability, self-healing properties and good tensile properties due to the effect of reversible cross-linking bonds. At present, some classic dynamic cross-linking bonds, such as Schiff base reaction and hydrogen bond, have been reported. Chinese patent CN112206345A, published on January 12, 2021, discloses a sustained-release multi-cross-linked hydrogel dressing, a preparation method and application thereof, which can be used to promote wound repair. Another Chinese patent CN114213682A, published on March 22, 2022, discloses a fish skin gelatin-based glycolipid hydrogel with dual dynamic cross-linking, a preparation method and application thereof, which improves the mechanical properties of gelatin-based hydrogels and makes them injectable, self-healing and adhesive. At the same time, the gelatin-based hydrogel prepared by this method has the characteristics of excellent biocompatibility, antibacterial function and simple operation. However, the development of dynamic hydrogels often requires a complex manufacturing process, especially for naturally derived polymers due to their limited reactive groups, which compromises their inherent biocompatibility or bioactivity. Therefore, designing a green, safe, and simple strategy for multifunctional natural polymer-based hydrogel dressings is necessary but remains a great challenge in clinical practice.

[0005] However, there is no report on the double dynamic cross-linked hydrogel for sustained-release of coral phytosalis lactone in the present application and its preparation method and application. Summary of the invention

[0006] The first object of the present invention is to provide a method for preparing a double dynamic cross-linked hydrogel for sustained-release of choriocarpone in view of the deficiencies in the prior art.

[0007] The second object of the present invention is to provide uses of the hydrogel.

[0008] The third object of the present invention is to provide another use of the hydrogel.

[0009] To achieve the above first purpose, the technical solution adopted by the present invention is:

[0010] A method for preparing a double dynamic cross-linked hydrogel for sustained-release of choriocarp lactone, characterized in that it comprises the following steps:

[0011] a) dissolving protocatechuic aldehyde in a solvent to obtain a solution A;

[0012] b) dissolving ferric chloride powder in a solvent to obtain a solution B;

[0013] c) mixing the solution A and the solution B, adjusting the pH and reacting to obtain a complex solution C;

[0014] d) dissolving the keratin powder in a solvent to obtain a solution D;

[0015] e) dissolving 50 μg PP, 26.7 mg poly F127 and 13.3 mg poly F68 in 1 mL anhydrous ethanol to obtain a mixture solution E;

[0016] f) the mixture solution E was evaporated under reduced pressure by a rotary evaporator to obtain a film of the PP / F127 / F68 composite;

[0017] g) hydrating the film with 2 mL of deionized water and forming a micellar suspension by ultrasonic dispersion;

[0018] h) filtering the suspension through a 0.45 μm filter membrane to obtain PP-loaded micelles;

[0019] i) reacting the solution C with the solution D to obtain a hydrogel precursor solution;

[0020] j) Mix 200 μL of PP micelles with 800 μL of hydrogel precursor solution and let stand for a certain period of time.

[0021] An injectable keratin-based hydrogel is obtained.

[0022] As a preferred example, there is no order restriction for step a) and step b), and the solvents in steps a), b) and d) are independently selected from one or more of water, physiological saline and buffer solution.

[0023] As a preferred example, the pH of the solution C is 10, and the pH of the solution D is 7.4.

[0024] As a preferred example, the molar ratio of protocatechuic aldehyde to ferric chloride in steps a) and b) is 3:1, and in step e), the volume ratio of solution C to solution D is 3:20.

[0025] As a preferred example, the dissolution temperature in step a) is 80°C, and the dissolution temperature in steps b) and d) is 25°C.

[0026] As a preferred example, the hydrogel uses keratin, protocatechuic aldehyde and ferric chloride as base materials, and the keratin contains more free thiol groups.

[0027] As a preferred example, the hydrogel substrate can be a single keratin material, or a composite of keratin and other inorganic or organic materials.

[0028] To achieve the above second purpose, the technical solution adopted by the present invention is:

[0029] Application of a double dynamic cross-linked hydrogel for sustained-release of corallinaloids in the preparation of a drug for promoting wound healing in inflammatory diseases.

[0030] As a preferred example, the inflammatory disease wound is a wound caused by diabetes, vasculitis ulcer, chronic eczema, radiotherapy, trauma or bacterial or viral infection.

[0031] To achieve the third purpose above, the technical solution adopted by the present invention is:

[0032] Application of a double dynamic cross-linked hydrogel with sustained release of coral lactone in the preparation of an injectable biomedical hydrogel dressing that promotes healing

[0033] The present invention has the advantages that:

[0034] (1) The abundant thiol groups of keratin itself are utilized, and the composite can be cross-linked into a gel without chemical modification, and the preparation method is simple.

[0035] (2) The obtained keratin-based hydrogel has injectability, good viscosity, antibacterial properties, healing properties and good biocompatibility, and can promote the repair ability of skin wound tissue. It has broad application value in biomedicine, tissue engineering and drug delivery. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Attached Figure 1 Preparation and characterization of ker-PA / Fe hydrogel. (A) Photographs of keratin solution and PA / Fe complex solution; (B) Digital photographs and representative SEM images of ker-PA / Fe hydrogel (scale bar = 200 μm); (C) Average pore size obtained from SEM images; (D) Equilibrium swelling ratio of ker-PA / Fe hydrogel; (E) Digital photographs of hydrogel before and after compression; (F) Mechanical compression curve of hydrogel. (G) Strain scan of hydrogel, with strain ranging from 0.01% to 1000%; (H) Rheological test of hydrogel. NS indicates not significant, **p<0.01 and ***p<0.001.

[0037] Attached Figure 2 UV-visible spectra of PA / Fe complex at various pH.

[0038] Attached Figure 3 A photo of pure keratin that is broken

[0039] Attached Figure 4Figure 3 shows the tissue adhesion, injectability and self-healing ability of the hydrogel. (A) Schematic diagram of the lap shear test; (B) Adhesion strength of the hydrogel on pig skin with collagen as a control; (C) Photo of the hydrogel adhering to pig skin tissue under bending and torsion; Photo of the hydrogel adhering to the finger joint and adapting to the finger movement; (D) The hydrogel adheres to human skin. After peeling, no residue is left on the skin; (E) Shear thinning properties of the hydrogel; (F) The hydrogel is injected into a dish and a beaker with water through a syringe and a 26-gauge needle; (G) Photo of the self-healing ability of the hydrogel; (H) Rheological behavior of the hydrogel under alternating strain cycles from 1% to 1000%. (I) Schematic diagram of the healing mechanism of the hydrogel. Data are expressed as mean ± SD. NS indicates not significant, **p<0.01 and ***p<0.001.

[0040] Attached Figure 5 Photos of ker-PA / Fe 0.5 hydrogels adhered to mouse heart, liver, lung, and kidney tissues.

[0041] Attached Figure 6 Drug release, antibacterial ability and biocompatibility of hydrogels. (A) Iron release profile 3+ Inset: Image of hydrogel after immersion in PBS solution; (B) PP release profile of PA / Fe0.5 hydrogel at 37°C; (C) Antibacterial activity against Staphylococcus aureus detected by inhibition zone; (D) Colony images on agar plates after 24 h of contact with PBS, ker-PA / Fe 0.25, ker-PA / Fe 0.5, ker-PA / Fe1, and ker-PA / Fe / PP 0.5; (E) Bacterial viability of hydrogel; (F) Hemolytic behavior of hydrogel. Inset: Image of hemolytic behavior of hydrogel with PBS as negative control and deionized water as positive control; (G) Viability of L929 mouse fibroblasts after incubation in leaching solution for 1 day, 3 days, and 5 days; (H) Live / dead staining results of L929 mouse fibroblasts. Scale bar = 100 μm. Data are expressed as mean ± standard deviation. NS indicates not significant, *p<0.05, **p<0.01, ***p<0.001 and ****p<0.0001.

[0042] Attached Figure 7 In vivo application of PP-loaded hydrogels in diabetic wound healing. Wounds were treated with saline (control), pure keratin hydrogel, ker-PA / Fe hydrogel, and PP+urea ointment, respectively. (A) Schematic diagram of the wound healing assay timeline; (B) Representative photos of wounds at different treatments on days 0, 3, 5, 7, and 10; (C) Quantitative analysis of wound healing rate based on wound area.

[0043] Attached Figure 8 The inhibitory effect of ker-PA / Fe / PP 0.5 hydrogel on re-epithelialization of diabetic wounds. (A) Representative H&E staining of wounds that received different treatments on day 10 after injury. The black dashed line indicates the edge of the wound; Scale bar = 500 μm, n = 3 samples / group; (B) Representative H&E staining of wounds that received different treatments on days 5 and 10 after injury. The black dashed line outlines the edge of the wound. The green dashed line highlights the migration of the epithelial tongue. Scale bar = 250 μm, n = 3 samples / group; (C) According to Figure 6 A Quantification of the remaining wound width on day 10; (DE) Quantification of the remaining wound width on day 5 and day 10 Figure 6 B Quantification of epithelial tongue migration length. Data are presented as mean ± SD. *p < 0.05, **p < 0.01, ***p < 0.001 and ****p < 0.0001.

[0044] Fig. 9 Effects of ker-PA / Fe / PP 0.5 hydrogel on collagen deposition in diabetic wounds. (A) Representative Masson staining of wounds receiving different treatments at 5 and 10 days after injury. Scale bar = 100 μm, n = 3 samples / group; (BC) Quantification of collagen density in wounds with different treatments at 5 and 10 days after injury. Data are expressed as mean ± SD. **p < 0.01, ***p < 0.001 and ****p < 0.0001.

[0045] Fig.10 Effects of ker-PA / Fe / PP 0.5 hydrogel on M1 / M2 polarization of macrophages in diabetic wounds. (A) Immunofluorescence staining of M1 macrophages stained with F4 / 80 (green) and iNOS (red) and macrophages in wound tissue stained with F4 / 80 (green) and CD206 (red) at day 5 after injury. Nuclei were stained with DAPI (blue). Scale bar = 50 μm, n = 3 samples / group; (B-C) Quantitative analysis of M1 and M2 macrophages in wounds with different treatments at day 5 after injury; (D) M1 / M2 ratio of macrophages Data are presented as mean ± SD. *p < 0.05, **p < 0.01 and ****p < 0.0001.

[0046] Fig.11Figure 5 shows the mRNA transcripts of inflammatory-related cytokines after different treatments on day 5 after injury. (AC) Pro-inflammatory factors of macrophage-related IL-1β, TNF-α and IL-6. (DE) Anti-inflammatory factors of macrophage-related IL-4 and IL-10. (F) Neutrophil chemokine CXCL-1. (GI) Signaling molecules related to the NF-κB signaling pathway of TLR2, TLR4 and MyD88. n=3samples / group. Data are expressed as mean ± SD. *p<0.05, **p<0.01, ***p<0.001 and ****p<0.0001. DETAILED DESCRIPTION

[0047] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0048] Example 1 Preparation and Application of Hydrogel

[0049] 1.1 Preparation and characterization of hydrogels

[0050] 1.1.1 Materials

[0051] Keratin was extracted from duck feathers, and protocatechuic aldehyde (PA), chordate lactone (PP), and collagen (bovine tendon type I collagen) were purchased from Shanghai Yuanye Technology Co., Ltd. (China). FeCl 3 Purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0052] 1.1.2. Preparation of iron complexes

[0053] The preparation of PA / Fe composite was carried out according to the literature [1]. PA was dissolved in deionized water at 80 °C and mixed with FeCl 3 A mixed solution was prepared at a molar ratio of 3:1. Subsequently, the pH value of the mixture was adjusted to 10.0 with sodium hydroxide solution (1 M). After stirring at room temperature for 3 hours, a PA / Fe mixture was obtained and analyzed using a UV / visible spectrophotometer.

[0054] 1.1.3. Preparation of polyiron hydrogel

[0055] 0.15 g of keratin was dissolved in 1 mL of deionized water to obtain a 15 w / v% keratin solution. Subsequently, different concentrations of PA / Fe complex solutions were added to the keratin solution to adjust the final concentration of PA in the hydrogel to 0.25, 0.5, and 1 w / v%, respectively. After stirring for a few seconds, the mixture was formed into a hydrogel at room temperature. The synthesized hydrogels were recorded as ker-PA / Fe 0.25, ker-PA / Fe 0.5, and ker-PA / Fe 1, respectively.

[0056] 1.1.4 Scanning electron microscopy observation

[0057] The microstructure of the hydrogel was observed by scanning electron microscopy (SEM) (HITACHI / TM-1000). Before observation, the hydrogel was freeze-dried and sprayed with gold. Based on the SEM images, the pore size of the hydrogel was measured using Image J software.

[0058] 1.1.5 Expansion Capacity

[0059] The swelling behavior of ker-PA / Fe hydrogel was measured at 37°C by immersing the hydrogel (5 mm in height and 10 mm in diameter) in 5 mL of PBS (0.01 M, pH 7.4). At certain intervals, the hydrogel was taken out of the PBS solution and weighed after wiping the superficial water with filter paper. The porosity was calculated using the following formula: (M1-M0) / M0×100%, where M0 and M1 represent the weight of the hydrogel before and after swelling, respectively.

[0060] 1.1.6 Compression test

[0061] Mechanical testing of the hydrogels was performed at room temperature using an electronic universal testing machine (Instron 5567, Norwood, MA). The prepared hydrogel samples were cylindrical with a height of 8 mm and a diameter of 10 mm. The compression rate was 5 mm / min and the strain varied from 0 to 85%.

[0062] 1.1.7 Rheological test

[0063] Rheological tests were performed on a rheometer (HAKKE MARS 60). Before the test, the hydrogel with a diameter of 8 mm and a height of 1 mm was placed on parallel plates. The linear viscoelastic region with a strain range of 0.01% to 1000% was determined by a strain amplitude sweep test. The frequency sweep test conditions were set to constant strain 1%, constant frequency 1 Hz, temperature 25 °C, and frequency sweep range 0.1-100 rad / s. In order to show the shear thinning characteristics, a continuous ramp shear rate (0-100s -1 ) to measure viscosity.

[0064] 1.1.8 Hydrogel adhesion strength test

[0065] The adhesion strength of the hydrogel to pig skin was measured by lap shear test. Fresh pig skin tissue was cut into rectangles with a width of 10 mm and a length of 30 mm and immersed in PBS for 1 h before use. 100 μL of ker-PA / Fe hydrogel was applied between two pieces of pig skin. The bonding area was 10 mm × 10 mm. After the pig skin was placed at room temperature for 1 h, the adhesion strength was tested by lap shear test at a speed of 2 mm / min on an electronic universal material testing machine (Instron 5567, Norwood, MA) with a 50 N load cell. Collagen gel was set as a control and prepared according to the literature [2].

[0066] 1.1.9 Injectability and self-healing ability test

[0067] Prepare hydrogels according to the preparation method described in 1.1.3 and test their injectability and self-healing ability.

[0068] 1.1.10 Preparation of Coralline Lactone-Loaded Hydrogel

[0069] PP loaded F127 / F68 mixed micelles were prepared by thin film hydration method to improve their water solubility. 50 μg PP, 26.7 mg poly F127 and 13.3 mg poly F68 were dissolved in 1 mL of anhydrous ethanol to form a clear and transparent solution. The mixture was subsequently evaporated by a rotary evaporator under reduced pressure to obtain a thin film of PP / F127 / F68 complex. The film was then hydrated with 2 mL of deionized water and a micellar suspension was formed by ultrasonic dispersion. The suspension was filtered through a 0.45 μm filter membrane to obtain PP loaded micelles. The PP concentration was determined to be 10 μg / mL using a UV spectrophotometer. To prepare PP loaded hydrogels, 200 μL of PP micelles were mixed with 800 μL of hydrogel precursor solution and then left statically to form hydrogels. The synthesized hydrogel was recorded as ker-PA / Fe / PP 0.5 with a final concentration of PP 2 μg / mL.

[0070] 1.1.11Fe 3+ and the release profile of choriolide

[0071] Fe 3+ The release of Fe was determined by incubating the hydrogels in 5 mL of PBS solution at 37 °C. 3+ The prepared sample was cylindrical with a diameter of about 10 mm and a height of about 3 mm. At a predetermined time point, the release medium was collected and Fe was determined by inductively coupled plasma spectrometry. 3+ concentration and replaced with an equal volume of fresh PBS solution.

[0072] Release of sphaerolide: The release profile of sphaerolide from the hydrogel was determined by incubating the drug-loaded hydrogel in saline. The samples were prepared as cylinders with a diameter of about 2 cm and a height of about 2 mm and placed in the wells of a 24-well plate. Then 2 mL of saline was added to the top of the hydrogel and incubated at 37 °C. At predetermined time points, the release medium was collected, the concentration of PP was determined by high performance liquid chromatography (HPLC), and then replaced with the same volume of fresh saline.

[0073] 1.2 Application of hydrogel

[0074] 1.2.1 Evaluation of antimicrobial activity

[0075] Staphylococcus aureus (S. aureus) was used as a model bacterium, and the antibacterial activity of the hydrogel was evaluated by the zone inhibition test and the diffusion plate colony count test. For the inhibition zone test, 100 μL of bacterial suspension (10 8 CFU / mL) was dropped onto an agar plate and spread. Then, the sterilized hydrogel sample was placed on an agar plate and incubated at 37°C for 24 h. Finally, an inhibition zone around the hydrogel was observed. For the spread plate colony count assay, 500 μL of the hydrogel was added to a 48-well microplate. Then, 100 μL of the bacterial suspension (10 5 CFU / mL) and 100 μL of sterilized PBS were added to the surface of the hydrogel disk and incubated at 37°C for 24 h. Finally, the live bacteria were resuspended with sterilized PBS and cultured on agar plates at appropriate dilutions to count the number of live bacterial colonies.

[0076] 1.2.2 In vitro blood compatibility evaluation

[0077] Mouse blood was centrifuged at 1500rpm to obtain red blood cells. Subsequently, the obtained red blood cells were washed three times with PBS and diluted to a concentration of 5v / v%. 500μL of hydrogel was added to 500μL of red blood cell solution and incubated in an incubator at 37°C and 100rpm for 1 hour. Deionized water and PBS solutions were used as positive and negative controls, respectively. Afterwards, the mixture was centrifuged at 1000rpm for 10 minutes. The absorbance of the supernatant was measured at 540nm by an enzyme marker. The hemolysis rate was calculated by the following formula: Hemolysis rate (%) = [(As-Al-Ap) / (Aw-Ap)] × 100%. As, Al, Aw and Ab are the absorbance values ​​of the supernatant treated with hydrogel, the leachate of the hydrogel in PBS, the supernatant treated with deionized water, and the supernatant treated with PBS, respectively.

[0078] 1.2.3 Compatibility evaluation of hydrogel

[0079] The cytocompatibility of ker-PA / Fe hydrogels was tested on L929 mouse embryonic cells using CCK-8 and live / dead assays. Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 10% fetal bovine serum (FBS) was used, and 1.0 × 10 5 UL -1 Penicillin and 100 mg / L streptomycin were used as complete growth medium. The freeze-dried ker-PA / Fe hydrogel was sterilized under UV light for 24 h, and 20 mg of the hydrogel was soaked in 10 mL of DMEM complete growth medium for 24 h to obtain the extracted solution. L929 cells were seeded into 96-well plates at a density of 5000 cells / well. After culturing at 37 °C in an incubator for 24 h, the culture medium was removed and the leached solution of the hydrogel was supplemented. For CCK-8 assay, when the cells were cultured for 1, 3, and 5 days, the culture medium in the wells was aspirated, and 100 μL of DMEM culture medium with 10% CCK-8 dye was added to each well. After incubation in a 37 °C incubator for 1 h, the absorbance value of the solution was measured at a wavelength of 450 nm using a microplate reader. 100 μL of Calcein-AM / PI dye was added to each well under dark conditions. After incubation at 37 °C for 25-30 min, the cell morphology was observed and photographed using an inverted fluorescence microscope.

[0080] 1.2.4 Evaluation of diabetic wound healing in vivo

[0081] The diabetic wound healing test was used to evaluate the therapeutic effect of the hydrogel. The animal experiments were approved by the Animal Care and Use Committee of Donghua University. Male C57BL / 6J mice (6-8 weeks old) were used, and the specimens were obtained from Shanghai Jiesijie Experimental Animal Co., Ltd. These mice were first adapted for one week before testing. The mice were intraperitoneally injected with low-dose streptozotocin (50 mg / kg of STZ dissolved in 0.5 mol / L, pH 4.5 sodium citrate buffer) every day for 7 consecutive days to induce type 1 diabetes. One week after the last injection of STZ, mice with blood glucose levels >16.7 mmol / L were considered to be successfully modeled diabetic mice. After disinfection with 75% alcohol, a full-thickness circular wound (about 6 mm in diameter) was created in the dorsal area with surgical scissors. Subsequently, the wounds were treated with sterile PBS solution (0.01 mol / L, pH 7.4), pure keratin hydrogel, ker-PA / Fe hydrogel, ker-PA / Fe / PP 0.5 hydrogel, and urea cream, and the dressings were changed every 3 days. The wounds were photographed on days 0, 3, 5, 7, and 10 and measured using Image J software. The wound healing rate was calculated as follows: Wound healing rate (%) = (A0-At) / A0×100%, where A0 and At are the wound areas on day 0 and at the designated time point, respectively. On days 5 and 10 after treatment, wound tissues were collected for further analysis.

[0082] 1.2.5 Re-epithelialization assessment

[0083] Hematoxylin and eosin (H&E) staining was used to evaluate the re-epithelialization of mouse skin tissue. On days 5 and 10, mice were sacrificed and wound tissue samples (including surrounding normal skin) were collected. The samples were then fixed in paraformaldehyde for 24 hours, embedded in paraffin and sectioned at the longest diameter of the wound. The sections were stained with hematoxylin (0.2%) and eosin (1%). Images were recorded using NanoZoomer S210 (Hamamatsu, Japan). The wound width and epithelial tongue extension were quantified to evaluate the level of skin re-epithelialization.

[0084] 1.2.6 Collagen evaluation

[0085] The treatment of mouse wound tissue was the same as that of hematoxylin-eosin staining. Masson trichrome staining was performed according to the instructions of the Masson staining kit (ZCIC120, Zuocheng Bio). Images were recorded by NanoZoomer S210 (Hamamatsu, Japan). Quantification was performed using Image-Pro Plus 6.0 analysis software. Quantification of skin collagen staining density was used to assess the maturity of collagen.

[0086] 1.2.7 Assessment of Macrophage M1 / M2 Polarization

[0087] Macrophages in wound tissue were analyzed in situ using monocyte / macrophage markers F4 / 80 and iNOS (M1 macrophages) or F4 / 80 and MMR / CD206 (M2 macrophages) markers for immunohistochemistry (IHC) evaluation of diabetic mouse skin on day 5. The treatment of mouse wound tissue was the same as hematoxylin-eosin staining. Primary antibodies F4 / 80 (#70076, CST), iNOS (ab283655, abcam) and CD206 (ab64693, abcam), secondary anti-peroxidase AffiniPure Goat Anti-Rabbit IgG (H+L) (JACKSON, 111-035-003) and DAPI (Sigma, D9542) were used for staining. Images were recorded by PANNORAMIC MIDI II (3D Histech, Hungary).

[0088] 1.2.8 Evaluation of inflammation-related factors

[0089] Real-time fluorescence quantitative PCR experiments were used to evaluate the relative mRNA expression of inflammatory factors. The wounds and surrounding skin of mice with diabetic ulcers were obtained on day 5, and total RNA was extracted and purified from the mouse skin using TRIzol reagent (Invitrogen, San Diego, CA, USA). The total RNA concentration was measured using Multiskan Go (Thermo Scientific). The total sample RNA was reverse transcribed into cDNA using PrimeScript RT Premix Kit (TAKARA) according to the manufacturer's instructions. Real-time PCR analysis was performed using SYBR Premix Ex Taq II (TAKARA). The primer sequences used for RT-PCR are listed in Table 1. The expression of the target gene was normalized using 18S. 2 -ΔΔCt Methods The changes in each group relative to the control group were calculated.

[0090] Table 1 Primer sequences used for real-time fluorescence quantitative PCR

[0091]

[0092] 3 Statistical analysis

[0093] All results are expressed as mean ± SD. (n ≥ 3) Multiple comparison analysis of variance (Prism8GraphPad) was used to evaluate significant differences. The differences between the two groups were statistically significant (*p < 0.05, **p < 0.01, ***p < 0.001, ****p < 0.0001).

[0094] 4 Results and discussion

[0095] 4.1 Preparation and characterization of hydrogels

[0096] The keratin solution was mixed with protocatechuic aldehyde (PA) and FeCl 3 The keratin was extracted from duck feathers and purified according to previous work. The free thiol concentration in keratin was estimated to be about 0.23 μmol / mg based on the Ellman test [3]. PA / Fe was synthesized by dynamic cross-linking of catechol in PA and Fe. 3+ Composite. By PA and FeCl 3 Physical mixing of the two groups of PA / Fe and Fe / Fe ... Figure 2). At pH 6.0, the product was mainly a di-iron catechol complex with a characteristic peak at 565 nm, while at pH 2.0, the product was mainly a mono-iron catechol complex with a peak at 725 nm. In this study, a PA / Fe tri-complex was obtained at pH 10.0. The resulting PA / Fe tri-complex was further mixed with a keratin solution, so that the aldehyde group in protocatechuic aldehyde and the thiol group in keratin formed a hydrogel at room temperature through a reversible thiol addition reaction ( Figure 3 In this way, ker-PA / Fe hydrogels were formed with a dual dynamic cross-linked network consisting of catechol-metal ion coordination and mercaptoaldehyde addition. Figure 1 B shows that solid brown ker-PA / Fe hydrogels were obtained at 15 w / v% keratin and different PA / Fe tri-complex concentrations (final PA concentrations were 0.25, 0.5, and 1 w / v%, ker-PA / Fe 0.25, ker-PA / Fe 0.5, and ker-PA / Fe1, respectively). All hydrogels have porous and reticular microstructures, as observed by scanning electron microscopy ( Figure 1 B). As the concentration of PA / Fe complex increases, the average pore size of the hydrogel ranges from ~160 to ~70 μm, indicating that the cross-linking density of the hydrogel network increases when the concentration of PA / Fe complex increases ( Figure 1 C). The average pore size of the ker-PA / Fe 0.5 hydrogel was approximately 120 μm, which is suitable for cell attachment and growth. The swelling ratio of the hydrogel further confirmed the microstructural results. At higher levels of PA / Fe complex, lower swelling ratios were achieved, which means that the density of network cross-linking was higher ( Figure 1 D). Figure 1 E shows a photograph of the ker-PA / Fe 0.5 hydrogel after compression and release. This hydrogel can withstand about 85% compression without obvious fracture and recovers to its original shape after the compressive force is removed. In addition, the hydrogel can be stretched to about 400%, indicating high elasticity. In contrast, the pure keratin hydrogel is too brittle and breaks when compressed to 85% ( Figure 3 ). Compression tests showed that all ker-PA / Fe hydrogels were intact under a strain of about 80%, and their maximum compressive strength showed a positive trend with the PA / Fe complex concentration due to the increase in cross-linking density in the hydrogel ( Figure 1 F). The rheological properties of the hydrogels were investigated by rheological tests. Before testing, we determined the linear viscoelastic region of the hydrogels and selected a strain of 1% for further testing ( Figure 1 G). Figure 1H shows that the higher the level of PA / Fe complex, the higher the storage modulus (G') of the hydrogel, indicating that the stiffness of the hydrogel is higher. At the same time, the tanδ values ​​(G" / G') of all hydrogels at all frequencies are less than 1, indicating the elastic properties of the hydrogel.

[0097] 4.2 Tissue adhesion, injectability, and self-healing ability of hydrogels

[0098] Lap shear tests were performed on two strips of fresh porcine skin on a mechanical testing machine to determine the adhesion capacity of the hydrogels ( Figure 4 A). As the concentration of PA / Fe complexes increases, the adhesion strength of the hydrogel increases, ranging from 10 kPa to 23 kPa, exceeding the adhesion strength of collagen ( Figure 4 B). Literature shows that both aldehyde and catechol groups contribute to the good adhesion strength of the hydrogel. At the same time, the hydrogel can not only adhere to the surface of the finger, but also adapt well to the movement of the finger without falling off ( Figure 4 C). It is noteworthy that the adhesion is mild, so that the hydrogel can be easily removed from the skin, reducing pain and leaving no residue, ensuring that dressing changes are carried out in a convenient and painless manner ( Figure 4 D). In addition to skin, the hydrogel can also adhere to the heart, liver, lung or kidney tissue of mice ( Figure 5 ). Rheological tests showed that the viscosity of the hydrogel decreased significantly with increasing shear rate, indicating that the hydrogel has obvious shear thinning behavior ( Figure 4 E). This property ensures the good injectability of the hydrogel, which can be continuously injected in air or water via a syringe and a 26-gauge needle ( Figure 4 F). A macroscopic healing test was performed to evaluate the self-healing ability of ker-PA / Fe 0.5 hydrogel. Figure 4 G). A hydrogel disk was cut into two parts, and one part was stained with Coomassie Brilliant Blue for better observation. Then, the two parts were placed together with the cut surfaces in contact at room temperature. The hydrogel healed after 30 min without cracks and could be stretched after healing ( Figure 4 G). The self-healing properties of ker-PA / Fe 0.5 hydrogels were further evaluated by continuous cyclic strain tests (1% strain → 1000% strain → 1% strain) ( Figure 4 H). When 1000% strain is applied, the G' value of the hydrogel decreases and is lower than the G" value, indicating the collapse of the hydrogel network. Once the strain drops to 1%, G' returns to almost its original value, which means the recovery of the network. This cycle of collapse and recovery can be repeated at least three times. The unique dual dynamic cross-linked network gives the hydrogel good self-healing properties ( Figure 4 I) This property helps maintain the integrity of the hydrogels when they are injured by external forces or applied to sports wounds.

[0099] 4.3 Drug release, antibacterial ability and biocompatibility of hydrogels

[0100] Fe 3+ The release curve of Fe was measured by immersing ker-PA / Fe 0.5 hydrogel in PBS solution at 37 °C. 3+ The cumulative release of 72h reached about 35% ( Figure 6 A). Coral polyol (PP) was loaded into F127 / F68 mixed micelles to obtain good water solubility and added to ker-PA / Fe 0.5 hydrogels by physical mixing. The PP-loaded hydrogels were immersed in saline at 37°C and the release profile of PP was measured. After 24 h, the cumulative release of PP in ker-PA / Fe / PP 0.5 hydrogels reached about 20%. As time went on, the drug release rate slowed down, and the cumulative release rate at 72 h was 27.3%. ( Figure 6 B). The in vitro antibacterial ability of the hydrogels against Staphylococcus aureus (S. aureus) was determined by the inhibition zone test and colony count test. All ker-PA / Fe hydrogels containing PP showed obvious inhibition zones after 24 h ( Figure 6 C). Figure 6 D shows that the number of Staphylococcus aureus colonies in all hydrogels was drastically reduced. In particular, the bacterial survival rates of ker-PA / Fe 0.5 and ker-PA / Fe1 hydrogels were both less than 5% ( Figure 6 E), which may be Fe 3+ The in vitro biocompatibility of the hydrogels was evaluated by cytotoxicity and hemolysis tests. The cytotoxicity of the ker-PA / Fe hydrogels was investigated by quantitative cell viability assay using CCK-8 and qualitative live / dead assay on L929 mouse fibroblasts. Compared with the PBS group, all the hydrogels with or without PP showed no significant difference in cell viability on L929 cells after 1, 3, and 5 days of culture ( Figure 6 F), indicating that the hydrogel has good cell compatibility. Live / dead staining test confirmed the results of CCK-8 detection. The number of live cells (green) increased with the extension of culture time, and there were few dead cells (red) ( Figure 6 G). In addition, all hydrogels showed no obvious hemolysis phenomenon, and the hemolysis rate was less than 5% ( Figure 6 H).

[0101] 4.4 In vivo assessment of diabetic wound healing

[0102] Using an excised full-thickness diabetic wound model, the therapeutic efficacy of PP-loaded ker-PA / Fe hydrogels in C57BL / 6 mice was evaluated. Figure 7A). To establish a diabetic mouse model, streptozotocin (STZ) was intraperitoneally injected for 7 consecutive days to induce blood glucose exceeding 16.7 mmol / L for 1 week. Full-thickness wounds with a diameter of ~6 mm were formed on the back skin. The diabetic wounds were treated with normal saline (control group), pure keratin hydrogel, ker-PA / Fe 0.5 hydrogel, ker-PA / Fe / PP 0.5 hydrogel, and PP+urea ointment (DMSO-dissolved PP treatment). In this experiment, the PP concentration of ker-PA / Fe / PP 0.5 hydrogel and PP+urea ointment was the same, 2 μg / mL, and was changed every 3 days. Figure 7 B is a representative picture of wounds in different groups at 0, 3, 5, 7, and 10 days after injury. Obviously, the healing effect of all treatment groups was better than that of the control group. Based on the wound photos, the quantitative healing rate ( Figure 7 C). We found that ker-PA / Fe hydrogels had a higher healing rate than pure keratin hydrogels at each time point, which may be due to its injectability and tissue adhesion, which can completely fill the wound site. The addition of PP to both ker-PA / Fe hydrogels and urea ointment accelerated wound healing, indicating good anti-inflammatory effects. It is worth noting that the wound healing effect of ker-PA / Fe / PP 0.5 hydrogel was better than that of PP+urea ointment during the test period, despite the same drug concentration. This shows that ker-PA / Fe hydrogels can be used as good drug carriers due to their inherent wound healing therapeutic effects and good biocompatibility, while the formulation of urea ointment requires DMSO solvent to improve the water solubility of PP, which may have side effects on the wound. The wound surface of the ker-PA / Fe / PP 0.5 group was basically healed on the 10th day, while the healing rate of the control group was only 57.0%.

[0103] 4.5pp-loaded hydrogel promotes re-epithelialization and collagen deposition

[0104] Re-epithelialization of the epidermis is an important step in the wound healing process. On day 10, H&E staining was used to observe the re-epithelialization of wounds after different treatments ( Figure 8 A). From the quantitative reflection of the remaining wound width, ker-PA / Fe / PP 0.5 significantly accelerated the re-epithelialization of diabetic wounds, followed by PP+urea ointment, ker-PA / Fe 0.5 and pure keratin groups ( Figure 8 C). Figure 8 B is H&E staining showing the epidermal migration of each group. In addition, the migration length of the epithelial tongue of ker-PA / Fe / PP 0.5 increased significantly on the 5th and 10th days ( Figure 8 D and 8E). These results suggest that ker-PA / Fe / PP 0.5 can accelerate the re-epithelialization of diabetic wounds.

[0105] On days 5 and 10 after injury, collagen deposition was assessed by Masson staining to evaluate dermal regeneration in diabetic wounds ( Fig. 9 A). Obviously, among the five groups, the ker-PA / Fe / PP 0.5 group had the densest collagen deposition in the wound area ( Fig. 9 B and 9C), indicating that ker-PA / Fe / PP 0.5 hydrogel can promote collagen regeneration in diabetic wound skin.

[0106] 4.6 In vivo promotion of the transformation of macrophages M1 to M2

[0107] Macrophages play an important role in the smooth junction of inflammatory and proliferative stages, which differentiate from the classically activated M1 phenotype that exhibits pro-inflammatory properties to the selectively activated M2 phenotype with anti-inflammatory and tissue regeneration functions. Immunofluorescence staining of wound tissues on day 5 after injury verified the effect of PP hydrogel on the phenotypic transformation of macrophages ( Fig.10 A). PP+urea ointment, ker-PA / Fe 0.5 hydrogel and pure keratin hydrogel were also compared. Fig.10 As shown in A, the red fluorescence of iNOS was higher in ker-PA / Fe 0.5 hydrogel, pure keratin hydrogel and control group. The fluorescence was lower in ker-PA / Fe0.5 hydrogel and PP+urea ointment groups. This result was further confirmed by quantitative analysis of the fluorescence intensity of iNOS in the wound ( Fig.10 B). For CD206, the ker-PA / Fe / PP0.5 and PP+urea ointment groups showed stronger red fluorescence, followed by the ker-PA / Fe 0.5 hydrogel ( Fig.10 A and 10C). The results showed that the application of PP stimulated the transformation of M1 to M2, thereby resolving local inflammation and promoting wound repair.

[0108] 4.7pp-loaded hydrogel regulates the inflammatory microenvironment

[0109] Real-time fluorescence quantitative PCR was used to detect the concentration of chemokines related to inflammation. The relative mRNA levels of pro-inflammatory and anti-inflammatory factors in the wound were measured on the 5th day after different treatments. The results showed that all groups downregulated pro-inflammatory factors such as IL-1β, TNF-α and IL-6 ( Fig.11 AC), while up-regulating anti-inflammatory factors such as IL-4 and IL-10 ( Fig.11 D and E). Among them, the ker-PA / Fe / PP 0.5 group had the lowest pro-inflammatory factors and the highest anti-inflammatory factors. Neutrophils are also the main effector cells involved in the healing of damaged wounds. CXCL-1 is an important chemokine associated with neutrophil migration and activation. Fig.11F shows that the mRNA level of CXCL-1 in the ker-PA / Fe / PP 0.5 and PP+urea ointment groups was significantly decreased, indicating that the anti-inflammatory mechanism of ker-PA / Fe / PP0.5 may also be related to the inhibition of neutrophil migration and activation.

[0110] TLR2, TLR4 and MyD88 are classic upstream signaling molecules of the NF-κB signaling pathway. Under the stimulation of TLR2 and TLR4, MyD88 binds to the cytoplasmic part and activates the transcription factor NF-κB to induce inflammatory cytokines. To detect whether ker-PA / Fe / PP0.5 has anti-inflammatory effects and its relationship with the TLR2 / 4 / Myd88 signaling pathway, we detected the relative mRNA expression of TLR2, TLR4 and MYD88 and found that compared with the control group, the ker-PA / Fe / PP 0.5 group had a significant inhibitory effect on TLR2, TLR4 and MYD88 ( Fig.11 GI). Therefore, we speculated that ker-PA / Fe / PP 0.5 had an anti-inflammatory effect, which might be related to the inhibition of TLR2 / 4-MYD88-NF-κB signaling pathway.

[0111] References

[0112] [1]Liang Y, Li Z, Huang Y, Yu R, Guo B. Dual-Dynamic-Bond Cross-LinkedAntibacterial AdhesiveHydrogel Sealants with On-DemandRemovability for Post-Wound-Closure andInfectedWoundHealing.ACSNano.2021;15(4):7078-93.

[0113] [2]Lin

[0114] [3]Yang G, Yao Y, Wang X. Comparative study of kerateine ​​and keratosebased composite nanofibers for biomedical applications. Mater SciEngCMaterBiolAppl.2018;83:1-8.

[0115] The above is only a preferred embodiment of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention. These improvements and supplements should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a double dynamic cross-linked hydrogel for sustained release of choriocarp lactone, characterized in that: The following steps are involved: a) dissolving protocatechuic aldehyde in a solvent to obtain a solution A; b) dissolving ferric chloride powder in a solvent to obtain a solution B; c) mixing the solution A and the solution B, adjusting the pH and reacting to obtain a complex solution C; d) dissolving the keratin powder in a solvent to obtain a solution D; e) dissolving 50 μg of choriocarpone PP, 26.7 mg of poly F127 and 13.3 mg of poly F68 in 1 mL of anhydrous ethanol to obtain a mixture solution E; f) the mixture solution E was evaporated under reduced pressure by a rotary evaporator to obtain a film of the PP / F127 / F68 composite; g) hydrating the film with 2 mL of deionized water and forming a micellar suspension by ultrasonic dispersion; h) filtering the suspension through a 0.45 μm filter membrane to obtain PP-loaded micelles; i) reacting the solution C with the solution D to obtain a hydrogel precursor solution; j) 200 μL of PP micelles were mixed with 800 μL of hydrogel precursor solution and allowed to stand for a certain period of time to obtain an injectable keratin-based hydrogel.

2. The preparation method according to claim 1, characterized in that: There is no order restriction for step a) and step b), and the solvents in steps a), b) and d) are independently selected from one or more of water, physiological saline and buffer solution.

3. The preparation method according to claim 1, characterized in that: The pH of the solution C is 10, and the pH of the solution D is 7.

4.

4. The preparation method according to claim 1, characterized in that: The molar ratio of protocatechuic aldehyde to ferric chloride in the steps a) and b) is 3:1, and in the step i), the volume ratio of solution C to solution D is 3:

20.

5. The preparation method according to claim 1, characterized in that: The dissolution temperature in step a) is 80°C, and the dissolution temperature in steps b) and d) is 25°C.

6. Use of a double dynamic cross-linked hydrogel for sustained release of coralline lactone in the preparation of a drug for promoting wound healing of inflammatory diseases, characterized in that: The double dynamic cross-linked hydrogel for sustained-release of choriocarp lactone is prepared by the method described in any one of claims 1-5.

7. The use according to claim 6, characterized in that: The inflammatory disease wounds are wounds caused by diabetes, vasculitis ulcers, chronic eczema, radiotherapy, trauma or bacterial or viral infections.

8. Use of a double dynamic cross-linked hydrogel for sustained release of coralline lactone in the preparation of an injectable biomedical hydrogel dressing that promotes healing, characterized in that: The double dynamic cross-linked hydrogel for sustained-release of choriocarp lactone is prepared by the method described in any one of claims 1-5.

Citation Information

Patent Citations

  • Slow-release multi-crosslinking hydrogel dressing as well as preparation method and application thereof

    CN112206345A

  • Application of glehnia littoralis lactone in preparation of medicine for promoting healing of diabetic ulcer wound

    CN113952333A

  • Therapeutic nanoparticles and methods thereof

    US20170119814A1